Die baden-württembergische Landtagswahl vom 27. März 2011: Zäsur und Zeitenwende? - Gabriel, Oscar W.; Kornelius, Bernhard (Zeitschrift für Parlamentsfragen, 2011)
At the end of one of the most polarized electoral campaigns ever seen in the state's history, it was quite clear on the eve of election day that a new government of the Green and Social Democrat parties would be formed. After an uninterrupted period as leading governmental party, the Christian Democrats had to move to the opposition, although they had succeeded in holding the position of the far strongest political group in the State of Baden Wuerttemberg. The severe losses of the liberal party were a decisive factor in bringing about the change in government. For the first time in the German electoral history, the Greens turned out as the second strongest political party in a state parliament, while the Social Democrats ranked third with an electoral result which was even lower than the party's historically poor record in the previous election. The election result was brought about by a truly unusual constellation of factors. Apart from a widely held preference for a change in government, the Christian Democrats presented an extremely unpopular candidate for the Prime Minister's office. Moreover, the political agenda of the electoral campaign was extremely unfavorable for the governing coalition. The most important issue of the campaign was the abolition of nuclear energy which has always been a Green issue. Regarding the second important issue, the reconstruction of the Stuttgart main railway station, the electorate was sharply divided, which partly favored the Greens and the Christian Democrats. Economic issues, normally falling under the issue ownership of the Christian Democrats didn't play a role this time.